(untitled) (Journal of Philosophy Culture and Political Science, 2018)
“The logic of meaning” is one of the fundamental works of Gilles Deleuze, representing the basic principles and principles of his philosophy. His contemporaries Michel Foucault and Jacques Derrida called "The Logic of Meaning" the best philosophically work of Deleuze. Here basic concepts are introduced, a special methodological approach of the philosopher is implemented, the holistic philosophy of the event is revealed.